Razonabilidad de la cuenta de propiedad, planta y equipo en la Empresa Arrocera “Marianela de Fátima” del Cantón Samborondón durante el periodo 2023. - Moran Murillo, Silvia Nicole (2024)
This case study is in progress to show the reasonableness of the property, plant and equipment account of the rice company 'Marianela de Fátima' for the period 2023, this company is regulated by the institutions of the Ecuadorian state with the purpose of ensuring its correct functioning within the market. An asset such as property, plant and equipment is considered to be an asset that was acquired by the company through a purchase or construction; Said good must have a useful life of more than one year, that it generates economic returns in the future and that its value can be measured reliably. The initial measurement and the measurement in the process of its useful life is important for the reasonableness of the statements. financially, if the measurement is not carried out in accordance with international accounting standards, it will not be possible to have reasonableness in the accounting account. In the investigation, an interview and accounting analysis of the property, plant and equipment account were carried out, where it was evident that the company did not carry out a correct initial classification of the assets that are part of this group of assets, in addition, depreciation was not carried out with the percentages established by the internal revenue service, and the revaluation of the land was not carried out, due to this the company does not present a reasonableness of the Property, Plant and Equipment account.